PENYULUHAN DAMPAK MEDIA SOSIAL TERHADAP KONSEP DIRI REMAJA DAN UPAYA MENGATASI KRISIS IDENTITAS PADA SISWA SMK MUHAMMADIYAH PARAKAN - Istikhana Nurulhuda; Ikrimatul Amal; Wasvita Sari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: The increasingly massive use of social media among teenagers plays a significant role in shaping self-concept, both positively and negatively. This counseling aims to educate students of Muhammadiyah Parakan Vocational School about the impact of social media on self-concept and provide strategies in overcoming identity crises that can arise from excessive media exposure. Based on Charles Horton Cooley's Looking-Glass Self theory, teenagers tend to form their self-image through perceptions and feedback received from the social environment, including online media. In addition, Erik Erikson's psychosocial development theory explains that teenagers are in the stage of searching for identity (identity vs. role confusion), where they are vulnerable to experiencing role confusion due to social comparisons that occur in digital media. The methods used in this counseling include material presentation, interactive discussions, and simulations to help students understand and manage the influence of social media on their self-concept. The expected results of this activity are increased student awareness of the psychological impact of social media and their ability to build a healthier and more positive self-identity